Sexual Violence Against Children and Women: How their Rights Fulfilled? (Law Research Review Quarterly, 2021)
The implementation of juridical death penalty has been regulated in Law No 2 of 1964 about the procedures of criminal implementation dropped by courts within the General and Military courts. The implementation of law on the implementation of death penalty is still disputed. The debate over the existence and execution of death penalty has been linked to the human right, the effectiveness, and the purpose of persecution. Through the constructivism with ontology, epistemology, and methodology, it can answer the community’s understanding and philosophical basis of legislation on the implementation of the death penalty, as well as the dynamics of its relation in Riau province Indonesia. This study is expected to contribute the improvement of the deadly criminal code in the future. This study aims to analyze the protection for children and women on sexual violence cases in Indonesia. This study used a normative legal study, which analyze the laws and regulation concerning legal protection for women and children in Indonesia.